Does it Matter if the President Isn't Pious? White Evangelicals and Elite Religiosity in the Trump Era. Issue 4 (December 2022) - Thompson, Jack
Abstract: Trump's unwavering support among white evangelicals seems a contradiction considering his seeming irreligiosity and well publicized moral transgressions. This contradiction raises an interesting question concerning whether Trump represents something of a unique case when it comes to white evangelical evaluations of elite religiosity, or whether his support among the group indicative of a new era of evangelical support for candidates that does not assess religiosity as it used to. Drawing on contemporary debates from the religious psychology and Christian nationalism scholarship, I use data from Wave 61 of the American Trends Panel (ATP) to test whether white evangelicals who encounter threats to their religious identities are more likely to view that God played some role in Trump's election. Overall, I find that white evangelicals consider themselves minorities as a result of their beliefs. Most importantly, these beliefs condition white evangelical beliefs about God's role in Trump's election. Specifically, I find that increases in threat perceptions lead to an increase in the probability of a white evangelical believing that Trump's election was part of God's plan. These findings provide a new vantage point for understanding why so many white evangelicals view Trump's election as a divine outcome despite the fact they are indifferent to his irreligiosity.